Аналіз структури продуктивності колекційних зразків малопоширених видів пшениці - Моргун, В.В.; Січкар, С.М.; Починок, В.М.; Голік, О.В.; Чугункова, Т.В. (Фактори експериментальної еволюції організмів, 2015)
Aim. To analyze a collection of rare species of wheat and select samples with high levels of productivity elements for
use in breeding programs and creation of new varieties of spelt and emmer. Methods. Field and laboratory methods for
studying the structure of plant productivity. Results. The samples of spelt and emmer collections from the Plant Production
Institute nd. a. V. Ya. Yuryev of NAAS of Ukraine and other scientifi c institutions were examined and characteristics of
plant productivity structure elements were represented. Conclusions. Perspective forms of winter spelt as well as winter
and spring emmer with high levels of productivity and elements of it structure were selected for genetic improvement of
spelt, emmer and bread wheat.
Keywords: Triticum spelta L., T. dicoccum (Schrank) Schuebl., diversity, plant productivity structure.